Cinnamaldehyde supplementation in sows and their offspring: effects on colostrum and milk composition, performance, redox status and intestinal health - Junqi Jin; Shiya Liu; Qiang Zhou; Zhengfeng Fang; Yan Lin; Shengyu Xu; Bin Feng; Yong Zhuo; Hefeng Luo; Xiuming Liu; De Wu; Lianqiang Che (Journal of Animal Science and Biotechnology)
Abstract Background Maternal nutrition significantly influences offspring development. This study investigated the effects of maternal or post-weaning cinnamaldehyde (CA) supplementation in sows and their offspring on reproductive performance and health. Sixty sows, selected based on body condition score and parity, were randomly allocated to control or CA (500 mg/kg) diets from d 107 of gestation to d 24 of lactation. At weaning, 128 piglets were assigned to four groups (n = 8) based on weight and source litter for a 21-d experiment. The four groups were CON-CON (both sow and piglet on CON), CON-CA (sow on CON, piglet on CA), CA-CON (sow on CA, piglet on CON), and CA-CA (both sow and piglet on CA). Results Maternal CA supplementation tended to improve body weight (+ 15%, P = 0.09) and average daily gain (+ 21%, P = 0.07) of suckling piglets, along with increased levels of milk IgG (P = 0.01) and IgM (P = 0.02), colostrum crude fat (P = 0.01), and plasma glutathione peroxidase (GSH-Px) activity (P = 0.02) at farrowing. Moreover, maternal CA supplementation significantly improved plasma antioxidant capacity, expressions of intestinal barrier and anti-inflammatory genes, and gut microbiota structure of piglets at the end of suckling. Additionally, maternal CA supplementation increased the apparent total tract digestibility (ATTD) of crude protein (P < 0.01), gross energy (GE; P = 0.03), and dry matter (P = 0.01), improved jejunal sucrase activity (P < 0.01), villus height (P = 0.03), the ratio of villi height to crypt depth (P = 0.02), and the expressions of intestinal barrier and anti-inflammatory genes in post-weaning piglets. Furthermore, post-weaning CA supplementation tended to decrease diarrhea scores of piglets during d 14–21 and increased the ATTD of GE (P = 0.02), activities of jejunal sucrase (P = 0.02), plasma catalase (P = 0.01), and total superoxide dismutase (P < 0.01) in piglets. Conclusion Maternal CA supplementation tended to increase the growth rate and weaning weight of suckling piglets, associated with improved antioxidant capacity and milk composition. Moreover, maternal CA supplementation or post-weaning CA supplementation improved nutrient digestibility, redox status, and intestinal function-related parameters of weaned piglets.